Comparison of control methods for a dynamic voltage restorer using a three-phase matrix converter. (December 2016) - Szcześniak, Paweł
A dynamic voltage restorer (DVR) is used in a power distribution system to protect sensitive loads against voltage disturbances. The commonly used DVR system contains a converter with direct current (DC) link and energy storage elements. The DC energy storage part of the system is the most expensive element and has a large value. As an alternative, therefore, DVR systems can use alternating current AC/AC converters without DC energy storage. This paper presents the properties of a DVR system based on a direct matrix converter using three control methods: in-phase, pre-sag, and energy-optimal. The paper defines basic mathematical relationships and static characteristics and describes the range of voltage compensation by use of the described compensation methods. Simulation results are obtained and presented in order to verify the correctness of the compensation. The features of such a DVR system configuration are considered in the context of alternative applications for commonly used converters with DC-link energy storage power converters. Application of the matrix converter in electrical power systems is still not very popular, due to limited output voltage and the complex structure and process control. This article is an attempt to show the usefulness of the matrix converter in spite of its limitations and the complexity of the design.